The Economic Impact of the Energy and Agricultural Complex on Greenhouse Gas Emissions in Kazakhstan - Smagulova, Sholpan Ð.; Adil, Junussov; Tanzharikova, Assem; Imashev, Aybek (International Journal of Energy Economics and Policy, 2017)
The work examines the impact of industrial activity on greenhouse gas emissions in Kazakhstan. There are two trends in the activity of the energy: the decline in energy production against the background of the crisis (1991-1999) and growth at the level of the increase in world oil prices (2000-2015). The analysis of the electric power industry and the sphere of agriculture as the main sources of environmental pollution have been carried out. The calculations of the relative changes in the total greenhouse gas emissions in the CO2 equivalent were calculated mathematically. High depreciation of fixed assets of power plants and agro-enterprises, high energy intensity of production, inefficient use of agricultural areas and a lack of investment inflow. The use of alternative types of energy, the introduction of "green" technologies, the withdrawal from hydrocarbon dependence, ensuring environmental safety of the companies of the fuel and energy complex and the agrarian sphere are justified. Keywords: greenhouse gas emissions, Kazakhstan, electric power, agriculture JEL Classifications: Q43, Q52, Q16